Association between dietary patterns and anemia in older adults: the 2015 China adults chronic diseases and nutrition surveillance - Pengfei Wang; Qiya Guo; Xue Cheng; Wen Zhao; Hongyun Fang; Lahong Ju; Xiaoli Xu; Xiaoqi Wei; Weiyi Gong; Lei Hua; Jiaxi Li; Xingxing Wu; et al. (BMC Public Health)
Abstract Background Anemia is a condition that has been affected 1.92 billion people worldwide in 2021, leading physical decline, functional limitation and cognitive impairment. However, there are currently fewer studies focusing on the relationship between anemia and dietary patterns in older adults. This study aimed to analysis the dietary patterns in older adults aged 60 and above in China and their association with anemia. Methods The data was obtained from the 2015 Chinese Adults Chronic Diseases and Nutrition Surveillance (2015 CACDNS), dietary information was collected using the food frequency method within the past year, exploratory factor analysis was used to extract dietary patterns, and logistic regression was used to analyze the relationship between dietary patterns and anemia. Results A total of 48,955 elderly people were included, and the number of anemia patients was 4,417 (9.02%). Four dietary patterns were categorized by the exploratory factor analysis, two dietary patterns have been found to have a statistically significant relationship with the prevalence of anemia. Compared to the first quintile, the fifth quintile of dietary pattern 2 (DP2), characterized by high intake of rice and flour, fresh vegetables, livestock and poultry meat, aquatic products, was associated with higher prevalence of anemia in older adults (OR = 1.412, 95%CI: 1.273–1.567, P < 0.0001), and the trend test results showed that score of this dietary pattern was associated with higher prevalence of anemia (p for trend < 0.0001). Compared to the first quintile, Dietary Pattern 4 (DP4), rich in fungi and algae, fried dough products, other grains, various beans, and rice and flour, was linked to lower prevalence of anemia of the fifth quintile (OR = 0.768, 95% CI: 0.674–0.874, P < 0.0001). And DP4 score was associated with lower prevalence of anemia (P for trend < 0.0001). Conclusions There were differences in dietary patterns among elderly people over 60 in China, and the prevalence of anemia in older adults was related to DP2, and DP4.